Dual functionality of pathogenesis-related proteins: defensive role in plants versus immunosuppressive role in pathogens - Han, Zhu; Schneiter, Roger (Frontiers in Plant Science, 2024)
Plants respond to pathogen exposure by activating the expression of a group of defense-related proteins known as Pathogenesis-Related (PR) proteins, initially discovered in the 1970s. These PR proteins are categorized into 17 distinct families, denoted as PR1-PR17. Predominantly secreted, most of these proteins execute their defensive roles within the apoplastic space. Several PR proteins possess well-defined enzymatic functions, such as β-glucanase (PR2), chitinases (PR3, 4, 8, 11), proteinase (PR7), or RNase (PR10). Enhanced resistance against pathogens is observed upon PR protein overexpression, while their downregulation renders plants more susceptible to pathogen infections.Many of these proteins exhibit antimicrobial activity in vitro, and due to their compact size, some are classified as antimicrobial peptides. Recent research has unveiled that phytopathogens, including nematodes, fungi, and phytophthora, employ analogous proteins to bolster their virulence and suppress plant immunity. This raises a fundamental question: how can these conserved proteins act as antimicrobial agents when produced by the host plant but simultaneously suppress plant immunity when generated by the pathogen? In this hypothesis, we investigate PR proteins produced by pathogens, which we term "PR-like proteins," and explore potential mechanisms by which this class of virulence factors operate. Preliminary data suggests that these proteins may form complexes with the host's own PR proteins, thereby interfering with their defense-related functions. This analysis sheds light on the intriguing interplay between plant and pathogen-derived PR-like proteins, providing fresh insights into the intricate mechanisms governing plant-pathogen interactions.